Nutritional Assessment of Invasive Alien Plants as Bioprospecting Resources in Mizoram, an Indo-Burma Mega Biodiversity Hotspot in India - Sengupta, Rabishankar; Dash, Sudhansu Sekhar; Seal, Tapan (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: The nutritional value, antinutritional properties, mineral and Vitamin content of six invasive Alien Plant species (IAPs) namely Ageratina adenophora, Ageratina riparia, Chromolaena odorata, Ocimum americanum, Bidens pilosa and Hyptis suaveolens which are used by the local inhabitants in Mizoram, India was analysed. Materials and Methods: The proximate composition, antinutritional contents, mineral and Vitamin content were investigated following standard analysis protocols. Tannins, saponins, oxalates, cyanogenic glycoside, and phytate were estimated to ascertain the antinutritional properties of the selected IAPs. Water soluble Vitamins were estimated by HPLC method and results were analysed utilising the Statistical Package SIGMAPLOT 14.5 (Systat Software Inc., USA). Results: Results revealed high protein (1.19-12.70%, dry plant material), carbohydrate (1.55-26.79%, dry plant material) and ash (6.93–12.14%) but low crude fat content (1.12–3.64%) in these IAPs. Highest Vitamin-C content was observed in A. adenophora (28.15 mg/ 100 g dry plant material). The oxalate content was maximum in A. riparia (0.29% ± 0.003%) and least in O. americanum (0.17% ± 0.002%); phytate content ranged from (0.06% ± 0.001%) in C. odorata to (0.11% ± 0.007%) in O. americanum. Tannin was detected highest in A. adenophora (3.82% ± 0.164%) and least in O. americanum (1.75% ± 0.024%). Highly invaded A. adenophora contained mineral in the following order Ca> Zn > K > Mg > Na > Fe > Mn > Cu. Conclusion: It can be concluded that these IAPs exhibited high nutritive value (high protein, carbohydrate content; micronutritional components Vitamin-C and minerals) of the examined plants. The study recommends these IAPs could potentially be used as a food or feed additive in Mizoram by locals for sustainable management of invasive plants.
Keywords: Invasive alien plants; Antinutrients; Mizoram; Minerals content; Proximate composition; Vitamin